Non‑native freshwater molluscs: a brief global review of species, pathways, impacts and management strategies - Manuel Lopes‑Lima; André Lopes‑Lima; Lyubov Burlakova; Karel Douda; Álvaro Alonso; Alexander Karatayev; Ng Ting Hui; Maxim Vinarski; Alexandra Zieritz; Ronaldo Sousa (Kluwer Academic Publishers, 2025)
Molluscs represent the second most diverse phylum on Earth and are among the most prevalent in freshwater ecosystems, exhibiting both high species richness and abundance/biomass. In addition, molluscs are one of the taxonomic groups with the highest number of non-native species in freshwater ecosystems. Many of these have significant ecological and economic impacts, and some also act as vectors for pathogens and parasites, affecting human and animal health. Here we provide a comprehensive list of all known freshwater mollusc species that have successfully established populations outside their native range, together with diversity pattern maps for both their native and invaded ranges. We also provide a brief overview of historical research investment, the main pathways of introduction, the ecological, economic and human health impacts of these species and the most effective strategies for the prevention of new introductions and for the control and possible eradication of already established populations. Finally, we highlight the gaps in our knowledge of the biology and management of non-native freshwater molluscs and future research needs and present a special volume dedicated to this topic.